Inositol 1,4,5-Trisphosphate Receptors in Hypertension - Eid, Ali H.; El-Yazbi, Ahmed F.; Zouein, Fouad; Arredouani, Abdelilah; Ouhtit, Allal; Rahman, Md M.; Zayed, Hatem; Pintus, Gianfranco; Abou-Saleh, Haissam (Frontiers in Physiology, 2018)
Chronic hypertension remains a major cause of global mortality and morbidity. It is a complex disease that is the clinical manifestation of multiple genetic, environmental, nutritional, hormonal, and aging-related disorders. Evidence supports a role for vascular aging in the development of hypertension involving an impairment in endothelial function together with an alteration in vascular smooth muscle cells (VSMCs) calcium homeostasis leading to increased myogenic tone. Changes in free intracellular calcium levels ([Ca2+]i) are mediated either by the influx of Ca2+ from the extracellular space and/or release of Ca2+ from intracellular stores, mainly the sarcoplasmic reticulum (SR). The influx of extracellular Ca2+ occurs primarily through voltage-gated Ca2+ channels (VGCC), store-operated Ca2+ channels (SOC), and Ca2+ release-activated channels (CRAC), whereas, SR-Ca2+ release occurs through inositol trisphosphate receptor (IP3R) and ryanodine receptors (RyR). IP3R-mediated SR-Ca2+ release, in the form of Ca2+ waves, not only contributes to VSMC contraction and regulates VGCC function, but is also intimately involved in structural remodeling of resistance arteries in hypertension. This involves a phenotypic switch of VSMCs as well as an alteration of cytoplasmic Ca2+ signaling machinery, a phenomena tightly related to the aging process. Several lines of evidence implicate changes in expression/function levels of IP3R isoforms in the development of hypertension, VSMC phenotypic switch, and vascular aging. The present review discusses the current knowledge of these mechanisms in an integrative approach, and further suggests potential new targets for hypertension management and treatment.